A NUMERICAL TAXONOMY OF Sida spp. (MALVACEAE) IN JAVA AND BALI ISLAND, INDONESIA - Felayati, Themas; Hery Purnobasuki (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Sida is a pantropical weed that can be annual or perennial. Several species have been identified in Indonesia. Sida cordifolia, S. rhombifolia, S. alnifolia, S. rhomboidea, S. acuta, S. glutinosa, and S. mysorensis were chosen for this study because they are representative of the species that are extensively spread in Indonesia. This study aims to update taxonomic information on the Sida genus in Indonesia. A phenogram was created using the data that was derived from the scoring of 70 morphological features. At PAST, the phenogram was created using cluster analysis, and Principal Cluster Analysis was used to determine the reason for clustering. The first cluster shows the separation of Sida acuta from all OTUs at a distance of 0.30. The second cluster shows the separation of OTU Sida cordifolia from OTU Sida glutinosa and OTU Sida mysorensis cluster at a distance between 0.20 until 0.25. The third cluster shows the separation of OTU Sida rhomboidea from OTU Sida rhombifolia and OTU Sida alnifolia cluster at a distance that was close to 0.20. The biggest value of PCA results is -0.45 and belongs to awn tip which is a character of mericarps. It demonstrates how crucial the mericarp trait is to identifying and appreciating the diversity of the genus Sida.